DEVELOPMENT OF LOW-COST WIRELESS ACCELEROMETER FOR STRUCTURAL DYNAMIC MONITORING - Galdino, Emerson; Cury, Alexandre (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Structural Health Monitoring (SHM) of civil infrastructures has great practical importance for engineers. Several researches have been carried out, such as the Rio-Niterói Bridge in Brazil, the former Z24 Bridge in Switzerland, the Millau Bridge in France, among others. In fact, some structures are monitored 24/7 to supply dynamic measurements that can be used for the identification of structural problems, such as the presence of cracks, excessive vibration, damage identification or even to perform life cycle analyses. SHM systems may provide automated assessments of structural health by processing data from sensors attached to the structure. SHM often uses wired systems, which are usually expensive due to the necessity of continuous maintenance and are not always suitable for sensing remote structures. On the other hand, commercial wireless systems often demand high implementation costs. In this sense, this paper proposes the development of a sensing system that uses an open-source prototyping platform (Arduino), which significantly reduces implementation costs while keeping data’s integrity. The wireless communication is performed in real time through a local wireless network, responsible for sending and receiving data. The proposed system is validated by comparing its results with a commercial wired system through an experimental application performed in laboratory.